Construction dewatering in a metro station incorporating buttress retaining wall to limit ground settlement: Insights from experimental modelling. (October 2021) - Zeng, Chao-Feng; Song, Wei-Wei; Xue, Xiu-Li; Li, Miao-Kun; Bai, Ning; Mei, Guo-Xiong
Highlights: Buttress retaining wall is used to limit deformations due to excavation dewatering. Laboratory tests are done to seek the deformation-control effect of buttress wall. Buttress wall can significantly reduce dewatering-induced ground surface settlement. Deformation-control effect is greater with buttress wall length increased. Deformation-control efficiency reduces as buttress wall length increases. Abstract: Dewatering with pumping wells placed inside an excavation is commonly adopted as groundwater control system to ensure the construction safety in water-rich strata. However, dewatering will cause both groundwater drawdown and retaining wall movement, which may together lead to serious ground settlement. Recently, a new earth retaining system, buttress retaining wall, is proposed to restrict the wall movement and the associated ground settlement induced by earth excavation, while its effectiveness in reducing dewatering-induced deformations is not investigated. A series of laboratory-scale experiments were performed based on a metro station to seek the effects of buttress retaining wall on ground settlement during construction dewatering. Miniature pumping wells were set up to effect the groundwater drawdown. The water level, pore water pressure, wall movement and ground surface settlement were monitored in real time, which were further compared quantitatively with flow net computation and some case records reported by former researchers. Results indicate that the use of buttress wall would significantly reduce the ground surface settlement due to foundation pit dewatering, and a greater reduction would appear in the case with longer buttress wall. However, in the condition with small drawdown incurred by dewatering, the deformation-restraining efficiency of buttress wall would reduce as its length increases.